The Influence of Oxygen Pressure on ZnO:Al Thin Films Properties Grown by Layer by Layer Growth Method at Magnetron Sputtering - Ievtushenko, A.I.; Klochkov, L.O.; Lytvyn, O.S.; Tkach, V.M.; Kutsay, O.M.; Starik, S.P.; Baturin, V.A.; Karpenko, A.Y.; Dusheyko, M.G.; Lashkarev, G.V.; Bykov, O.I. (Physics and Chemistry of Solid State, 2015)
The influence of oxygen pressure in the deposition chamber on the structure, morphology, optical and electrical properties of aluminum doped ZnO films deposited by a layer by layer growth method in magnetron sputtering on glass substrates was studied. The effect of the application of the traditional one-step approach and our proposed layer by layer growth method in magnetron sputtering on the properties of doped by aluminum ZnO films was analyzed. It is found that with decreasing oxygen pressure in the deposition chamber improves the structure, increases transmittance in the visible spectrum of radiation and decreases resistivity of ZnO:Al films. It is shown that the application of layer by layer growth method in magnetron sputtering allows to grow the transparent conductive ZnO:Al films with higher performance parameters, compared with the films which condensed by traditional approach in magnetron sputtering. The layer by layer growth method allows to grown ZnO:Al films with electrical resistance at 6.1·10-4 Ohm·cm and transmission in the visible light of 95%, which is promising for their aplication in photovoltaic devices.